2015
DOI: 10.1002/jcsm.12023
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin prevents tumour‐ and cisplatin‐induced muscle wasting: characterization of multiple mechanisms involved

Abstract: BackgroundCachexia and muscle atrophy are common consequences of cancer and chemotherapy administration. The novel hormone ghrelin has been proposed as a treatment for this condition. Increases in food intake and direct effects on muscle proteolysis and protein synthesis are likely to mediate these effects, but the pathways leading to these events are not well understood.MethodsWe characterized molecular pathways involved in muscle atrophy induced by Lewis lung carcinoma (LLC) tumour implantation in c57/bl6 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
220
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(244 citation statements)
references
References 56 publications
(96 reference statements)
18
220
3
Order By: Relevance
“…Also, the vagus nerve has been shown to mediate some of ghrelin's effects via the ghrelin receptor GHSR‐1a (Iwasaki et al ., 2015). Recently, an alternative—yet unidentified—receptor has been proposed as a mechanism for ghrelin to exert effects in vitro in hepatocytes, myocytes, or adipocytes (Chen et al ., 2015). The exact mechanism mediating ghrelin's effects in liver is not well characterized and should be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the vagus nerve has been shown to mediate some of ghrelin's effects via the ghrelin receptor GHSR‐1a (Iwasaki et al ., 2015). Recently, an alternative—yet unidentified—receptor has been proposed as a mechanism for ghrelin to exert effects in vitro in hepatocytes, myocytes, or adipocytes (Chen et al ., 2015). The exact mechanism mediating ghrelin's effects in liver is not well characterized and should be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that tumor implantation is associated with an increase in the expression of the ubiquitin ligases MAFbx/Atrogin-1 and MuRF1 (20). To investigate whether isofl avones suppress muscle wasting through ubiquitin ligase activation, we examined the expression of MAFbx/Atrogin-1 and MuRF1 mRNA levels in TN, CN, CI and TI mice.…”
Section: Effect Of Dietary Isofl Avones On Expression Of Atrophy-relamentioning
confidence: 99%
“…We have thus far evaluated a single rapid model of experimental cachexia which necessarily limits the broader interpretation of our findings. The short treatment window (<14 days) afforded by the C-26 model in our hands also severely curtailed our ability to demonstrate overt anabolic effects following GTx-024 treatment relative to other anabolic agents in less severe models [93]. Evaluation of combination treatment in other experimental models of cachexia are ongoing.…”
Section: Cc-by-nc-nd 40 International License It Is Made Available Umentioning
confidence: 98%
“…Likewise, the doses of GTx-024 used were higher than what would be expected to provide anabolic benefit [93]. Dose optimization is critical to both improve efficacy and minimize toxicity as the tolerance for additional side effects associated with anti-cachexia therapy in already heavily treated cancer patients is low.…”
Section: Cc-by-nc-nd 40 International License It Is Made Available Umentioning
confidence: 99%
See 1 more Smart Citation